Using Deep Learning for Obscene Language Detection in Vietnamese Social Media - Dang, Dai Tho (Springer Nature, 2023)
Lecture Notes in Networks and Systems (LNNS, volume 734); CITA: Conference on Information Technology and its Applications; pp: 306-317.